2010
DOI: 10.1007/s11414-010-9211-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Utility of Consumer Surveys for Improving the Quality of Behavioral Health Care Services

Abstract: The development and implementation of provider performance and consumer outcome measures for behavioral health care have been growing over the last decade, presumably because they are useful tools for improving service quality. However, the extent to which providers have successfully used performance measurement results has not been adequately determined. To this end, two methods were used to better understand the use of data obtained from an annual survey of behavioral health care consumers: a cross-sectional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 30 publications
0
24
0
Order By: Relevance
“…For example, clinicians and clients could concurrently complete and discuss the quality of care scales during treatment plan updates or during the completion of performance measures. 63 …”
Section: Implications For Behavioral Healthmentioning
confidence: 99%
“…For example, clinicians and clients could concurrently complete and discuss the quality of care scales during treatment plan updates or during the completion of performance measures. 63 …”
Section: Implications For Behavioral Healthmentioning
confidence: 99%
“…Approximately 42% (n=5) of the studies were conducted in the United States, while the remaining 58% (n=7) were carried out in Europe. Publication dates of the 12 papers ranged from 2003 to 2013 (Table 1 [13][14][15][16][17][18][19][20][21][22][23][24] ).…”
Section: Characteristics Of Included Articlesmentioning
confidence: 99%
“…• Benchmarking: Two studies 13,14 reported that survey findings were examined against results of other organizations and agencies.…”
Section: Post-data Collection and Analysis Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…This change in focus means that indicators which were once designed to measure at the institutional level must now also be reflective of the community level (Sandoval et al, 2012). All of this best practice information has created a substantial change in the structure of mental and substance use disorder care delivery in Canada and the VHA, and has also persuaded Ireland's HSE to consider a similar restructuring from inpatient to outpatient primary care services (Government of -14 - Table 2, may not be effectively captured as this data is often collected via survey/audit (Koch, Breland, Nash, & Cropsey, 2011). Furthermore, uploading of diagnosis-based events may not capture more subtle interventions within the encounter.…”
Section: Development and Content Of Kpis For Mesudsmentioning
confidence: 99%